2016
DOI: 10.5937/savteh1602018s
|View full text |Cite
|
Sign up to set email alerts
|

The oxidation of anthraquinone dye using HRP immobilized as a cross-linked enzyme aggregates

Abstract: Finding a sustainable and ecofriendly methods for recalcitrant synthetic dyes removal is a researchers` major challenge. A carrier-free technique for commercial HRP immobilization is a focus of the present study. The immobilized biocatalyst, HRP-CLEAs with 580 U g-1 of the activity was obtained under the following immobilization conditions: precipitation reagent 80% ammonium sulphate, cross-linking reagent 1% of glutaraldehyde and protein-fedder, bovine serum albumin (BSA) concentration 5 mg ml-1. The obtained… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 32 publications
(39 reference statements)
0
1
0
Order By: Relevance
“…In this study, investigation of anthraquinone dye AV109 biodegradation by horseradish peroxidase in a microreactor is performed. Previous research studies have shown that the optimal pH value for degradation of AV109 by peroxidase is 4 [16,17].…”
Section: Resultsmentioning
confidence: 98%
“…In this study, investigation of anthraquinone dye AV109 biodegradation by horseradish peroxidase in a microreactor is performed. Previous research studies have shown that the optimal pH value for degradation of AV109 by peroxidase is 4 [16,17].…”
Section: Resultsmentioning
confidence: 98%
“…Horseradish peroxidase (HRP) can be applied for treating dye wastewater. However, it is expensive and cannot work well under harsh conditions . In recent years, some artificial nanozymes, possessing a nanostructure and similar enzyme activity, have been successfully designed to overcome the disadvantages.…”
Section: Introductionmentioning
confidence: 99%